2002
DOI: 10.1111/j.1467-842x.2002.tb00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to poliomyelitis in Victorians

Abstract: Objectives: In view of WHO's goal for poliomyelitis eradication by 2005 and the possible introduction of IPV into the Australian Standard Vaccination Schedule, this investigation was conducted to assess current immunity to poliomyelitis across the Victorian community Methods: 1,775 sera collected from three population samples within the Victorian community between 1990 and 1995 were tested for neutralising antibody titres against each poliovir us type in accordance with WHO recommended procedure. Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
1
1
Order By: Relevance
“…Even so, it remains important to maintain herd immunity. Although the levels of immunity in this study, especially to poliovirus 3, are lower than in the earlier Victorian study, 11 they are much higher than those reported in serosurveys from NSW (in which the same laboratory method was used as in the present survey) in 1972, 1980 and 1982 [26][27][28] when there was no evidence that wild virus circulated. However, Finland experienced a small outbreak of type 3 infection in 1983 when only 60% of preschoolaged children were immune to type 3, 29 a similar level to that found in a small group of 101 vaccinated preschool-aged Aboriginal and Torres Strait Islander children in north Queensland in 1995.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Even so, it remains important to maintain herd immunity. Although the levels of immunity in this study, especially to poliovirus 3, are lower than in the earlier Victorian study, 11 they are much higher than those reported in serosurveys from NSW (in which the same laboratory method was used as in the present survey) in 1972, 1980 and 1982 [26][27][28] when there was no evidence that wild virus circulated. However, Finland experienced a small outbreak of type 3 infection in 1983 when only 60% of preschoolaged children were immune to type 3, 29 a similar level to that found in a small group of 101 vaccinated preschool-aged Aboriginal and Torres Strait Islander children in north Queensland in 1995.…”
Section: Discussioncontrasting
confidence: 76%
“…These estimates are lower than were found in sera collected, from various sources, between 1991 and 1995 in Victoria from subjects under the age of 40 years. 11 Depending on age, 90-100% of Victorians were seropositive to type 1, 94-100% seropositive to type 2 and 80-97% seropositive to type 3. This difference is unlikely to be due to the fact that the Victorian cohorts were born several years earlier than the national cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the production of inflammatory cytokines is altered during both PMV and PVS infection (data not shown). Therefore the question arises, how do individuals develop the strong and lasting immunity (29,50,52) associated with the Sabin vaccine? Several models can be hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies have been directed towards the protective neutralizing antibody response in various populations worldwide (6,10,15,28,45,49); less attention has been given to adaptive T-cell responses and the probable role of these cells in the resolution of PV infection.…”
Section: T-cell Responses In Vitro From Vaccinees Both Cd4mentioning
confidence: 99%